Antibiotic therapy of choice for community-acquired pneumonia in Malaysian Hajj pilgrims: the pattern and associated factors - Dzaraly, Diana; Rahman, Nor Iza A.; Haque, Mainul; Wahab, Mohd Suhaimi Bin Ab; Simbak, Nordin Bin; Aziz, Aniza Abd; Ismail, Salwani; Muttalif, Abdul Razak Abdul (Medical Studies/Studia Medyczne, 2017)
Introduction : Pneumonia is a potentially life-threatening illness that poses global health teething troubles particularly among elderly population and performing Hajj. Empirical antibiotic treatment has been recommended for all suspected community-acquired pneumonia (CAP) patients as initial treatment on admission. Aim of the research : To describe the antibiotic therapy of CAP and determine the associated factors related to the treatment options among Malaysian Hajj pilgrims. Material and methods: This was a cross-sectional study involving 91 patients who were admitted to Tabung Haji Hospital, Makkah in 2012, with the clinical diagnosis of pneumonia during Hajj season. The antibiotic treatment for the patients as well as demographic factors and co-morbidity, which potentially influence the treatment options, were studied. Results : The mean age of the hajj pilgrims was 71.4 ±8.7 years. The most frequently prescribed antibiotic was levofloxacin (44.0%), followed by azithromycin (40.7%), cefuroxime (23.1%), ampicillin + sulbactam (16.5%), and amoxicillin + clavulanate (15.4%). The age of patients was significantly associated with levofloxacin, azithromycin, and meropenem (p = 0.032, 0.028, and 0.026, respectively). Patients with diabetes were statistically significantly highly prescribed with cefuroxime (p = 0.036). Conclusions : Levofloxacin and azithromycin were classified as the most common antibiotic treatment given to Malaysian Hajj pilgrim with CAP and their choice was associated with older age of patients. Otherwise, cefuroxime was the prescription of choice in diabetics.